SINTESIS DAN KARAKTERISASI MATERIAL FOTOKATALIS Na2Ti6O13 MENGGUNAKAN METODE HIDROTERMAL - Cukri Rahma (Universitas Teuku Umar, 2017)
hydrotermal method. Hydrotermal method is environmentally frendly way. This matter becaused hydrothermal method is using materials that are safe for life. Sodium hexa titanate is a semiconductor matterial that is widely used in various fields, such as is used as a photocatalyst material. From the characterization results, Na2Ti6O13 with size of 48.44 nm, and energy gap of 3.40 eV has been prepared. Na2Ti6O13 has a monoclinic crystal system with lattice parameters of a = 15.210 Å, b = 3.744 Å, c = 9.165 Å, and β = 99.050o. Photocatalyst activity was tested under UV light irradiation for 3 hours. Degradation of methylene blue (MB) by Na2Ti6O13 is found to be at 51%.Keywords: Photocatalyst, Na2Ti6O13, Degradation methylene blue